Elevated congenital heart disease birth prevalence rates found in Central Vietnam and dioxin TCDD residuals from the use of 2, 4, 5-T herbicides (Agent Orange) in the Da Nang region - Hoang Thi Nam Giang; Tran Thanh Hai; Hoang Nguyen; Thanh K. Vuong; Lois Wright Morton; Casey B. Culbertson (Public Library of Science (PLoS), 2022)
Congenital heart disease (CHD) birth prevalence rate in Da Nang City and two adjacent provinces in Central Vietnam reported by Giang et al. in 2019 was 20.09/1000 births, much higher than any CHD birth rates previously reported. In this current study, three physicians trained in pediatric cardiology reanalyzed and reclassified the Giang et al 2019 cardiac anomalies data, eliminating singular small PDAs and separating cardiac defects into 27 contemporary CHD subgroups. These CHD subgroups were then statistically compared with Liu et al. 2019 Global CHD birth prevalence study of Asian Low-Middle Income Countries (LMIC) CHD subgroup rate of 9.34/1000 births (95% CI 8.07-10.70). Despite applying newer diagnostic criteria and refining the cardiac anomalies data, the Da Nang region continued to show significantly (p<0.0001) elevated total CHD birth prevalence rates at 14.71/1000 births (95% CI 12.74-16.69) compared to the Asian LMIC CHD birth prevalence rate 9.34/1000 births. This finding raises the question of whether environmental persistence of the contaminant dioxin TCDD from 2,4,5-T herbicides (Agent Orange) used during the Vietnam War (1961-1971) in the Da Nang region might be a factor associated with elevated CHD birth prevalence, as it is not present in other LMIC surrounding Vietnam. We recommend testing of soils and sediments in rural and agricultural areas in Central Vietnam that received high volume applications of contaminated herbicides to assess the relationship of the higher CHD birth prevalence rate and the presence of residual dioxin TCDD. Enhanced fetal cardiac echocardiograpy in the region to screen for CHD would enable early interventions and could improve outcomes for infants and children.